Hiroshima bugi : Atomu 57 - Vizenor, Gerald Robert, 1934- (Native storiers., 2003)
"Hiroshima Bugi: Atomu 57 is a kabuki novel that begins in the ruins of the Atomic Bomb Dome, a new Rashomon Gate. Ronin Browne, the humane peace contender, is the hafu orphan son of Okichi, a Japanese boogie-woogie dancer, and Nightbreaker, an Anishinaabe from the White Earth Reservation who served as an interpreter for General Douglas MacArthur during the first year of the American occupation in Japan."